A case study of payments for ecosystem services and the need for integrated catchment management: experiences from the Westcountry Rivers Trust - Laurence B. Couldrick (Cambridge Prisms: Water)
This case study uses the concept of ecosystem services and specifically payments for ecosystem services, alongside five experiences from the Westcountry Rivers Trust (WRT), which celebrates its 30th anniversary in 2024, to demonstrate the need for integrated catchment management (ICM). It highlights the multifaceted benefits that ecosystems provide to human well-being, the challenges faced in managing these often-siloed services and the role of ICM in preserving and enhancing multiple ecosystem services, focusing on the water-related drivers of flooding, drought, water quality and aquatic biodiversity. Through WRT projects this case study highlights practical applications and successes in managing ecosystem services at the catchment level and what considerations are needed for future integration and delivery of multi-benefit solutions. This paper is derived in part from the interviews and workshops undertaken as part of the Atlantic Area Interreg funded Triple C project (EAPA_772/2018), as well as contributions from the Horizon funded, InnWater project (Horizon EUROPE No. 101036683 and UKRI No. 10066637) and the OFWAT-funded, mainstreaming Nature-based Solutions.